Effects of Roxazyme G® and Maxigrain® on Performance, Egg Quality, Cost-Benefit and Haematological Parameters of Laying Hens Fed Wheat Offal, Corn Bran and Brewery Dry Grain Diets - Ademola , S.G.; Egbewande, O.O.; Lawal, T.E.; Isah, A.T.; Kuranga, S.M. (International Journal of Poultry Science, 2011)
The study examined effects of supplementing Roxazyme G® and Maxigrain® to wheat offal-, corn bran- and brewery dry grain-based diets on the performance, haematological parameters and economy of production in laying hens. Both enzymes were added to these 3 diets at 100 mg/kg, while control group was neither supplemented with Roxazyme G® nor Maxigrain®. The results showed that hens fed Roxazyme G® corn bran diets had the best feed conversion and maximum profit. Maxigrain® also significantly improved hen day production and egg weight of hens fed Brewery Dry Grain (BDG) than those fed Roxazyme G® BDG diet. Laying hens fed BDG diets had the lowest profits. Both enzymes failed to improve the performance and profits of hens fed Wheat Offal (WO) diet. Improvements in Red Blood Cells (RBC) for hens fed both enzyme supplemented diets were observed. Interactive effects of enzyme type and fibre source significantly (p<0.01) influence RBCs, PCV and white blood cells. The study revealed that Roxazyme G® and Maxigrain® should be added to respectively CB- and BDG- diets for improved laying performance. However, these enzymes failed to improve the laying performance of hens fed WO diet.